Rechargeable Aqueous Zinc-Ion Batteries in MgSO4/ZnSO4 Hybrid Electrolytes - Zhang, Yingmeng; Li, Henan; Huang, Shaozhuan; Fan, Shuang; Sun, Lingna; Tian, Bingbing; Chen, Fuming; Wang, Ye; Shi, Yumeng; Yang, Hui Ying (Nano-Micro Letters, 2020)
MgSO4 is chosen as an additive to address the capacity fading issue in the rechargeable zinc-ion battery system of MgxV2O5·nH2O//ZnSO4//zinc. Electrolytes with different concentration ratios of ZnSO4 and MgSO4 are investigated. The batteries measured in the 1 M ZnSO4−1 M MgSO4 electrolyte outplay other competitors, which deliver a high specific capacity of 374 mAh g−1 at a current density of 100 mA g−1 and exhibit a competitive rate performance with the reversible capacity of 175 mAh g−1 at 5 A g−1. This study provides a promising route to improve the performance of vanadium-based cathodes for aqueous zinc-ion batteries with electrolyte optimization in cost-effective electrolytes. Highlights: 1 Divalent magnesium ions as electrolyte additives are first used to improve the performance of vanadium-based cathodes for aqueous ZIBs. 2 Pre-adding magnesium ions into electrolytes provide an appropriate equilibrium balance between the dissolution and recombination of magnesium vanadates, thus suppress the continuous dissolution of active materials, and lead to a higher stability of the electrode. 3 The hybrid aqueous electrolytes with cost-effective ZnSO4 and MgSO4 salts show a better competitive prospective for the stationary grid-scale applications.